2011
DOI: 10.1111/j.1600-0714.2011.01031.x
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase-1 and -2 expression in mobile tongue squamous cell carcinoma: associations with clinicopathological parameters and patients survival

Abstract: The present study supported evidence that HDACs may participate in the formation and progression of mobile tongue SCC, reinforcing their possible use as biomarkers as also the therapeutic utility of HDAC inhibitors in mobile tongue SCC chemoprevention and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 55 publications
1
39
0
Order By: Relevance
“…Overexpression of HDAC1 (and not HDAC2) in tongue squamous cell carcinoma is associated with poor differentiation of stages and lymph node metastasis (47). The siRNA targeting HDAC1 in OSCC cell line led to a decrease in cell proliferation and an increase in cell apoptosis (48).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overexpression of HDAC1 (and not HDAC2) in tongue squamous cell carcinoma is associated with poor differentiation of stages and lymph node metastasis (47). The siRNA targeting HDAC1 in OSCC cell line led to a decrease in cell proliferation and an increase in cell apoptosis (48).…”
Section: Discussionmentioning
confidence: 99%
“…HDACs are involved in oral cancer formation and progression (47). Overexpression of HDAC1 (and not HDAC2) in tongue squamous cell carcinoma is associated with poor differentiation of stages and lymph node metastasis (47).…”
Section: Discussionmentioning
confidence: 99%
“…In oral tongue cancer (generally HPV-negative) it has been demonstrated that HDAC1 and 2 are overexpressed and associated with significantly shorter progression-free survival (PFS) [30]. Moreover, in several clinical studies the measurement of histone acetylation on PBMC has been studied as a surrogate marker of HDACi activity; however, in most cases this measurement has not been successfully linked to clinical outcome.…”
Section: Rationalementioning
confidence: 99%
“…[29] [34] [30] In this environment, psoriatic keratinocytes produce high quantities of VEGF via HIF-1alpha that is not ubiquitinated by VHL due to the intervention of HDAC1 and LL-37. e same phenomenon could be occurring in squamous cell carcinoma (SCC) as HDAC1 overexpression has been observed in this cancer [35] and because in oral squamous cell cancinoma, VEGF is over-expressed and is reg ulate d by H I F-1a lpha under hyp oxic conditions. [36][37] In the same way, the dysfunction of VHL is also associated with the development of tongue cancer [39] as well as in psoriasis.…”
Section: Discussionmentioning
confidence: 97%